Strategi Dakwah MUI Dalam Penanganan Aliran Menyimpang Di Kota Medan - Siregar, Odang Partahian; Sikumbang, Ahmad Thamrin (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2025)
The purpose of this descriptive qualitative research is to analyze the da'wah strategy implemented by the Indonesian Ulema Council (MUI) of Medan City in dealing with deviant sects that have the potential to disrupt the faith and harmony of the lives of Muslims. Through in-depth interviews with MUI administrators, religious figures, and analysis of documentation related to da'wah policies including field observations, the collected data were analyzed thematically. The results of the study indicate that the MUI of Medan City adopts a da'wah strategy that includes routine monitoring, intensive dialogue with ulama and community leaders, and cooperation with educational institutions and the media to disseminate clarification of deviant teachings. A persuasive and educational approach is the main key to straightening out public understanding peacefully. Despite facing challenges such as limited resources and the massive spread of deviant teachings on social media. With an adaptive and collaborative strategy, the MUI is advised to be optimal in maintaining the integrity of the faith and unity of Muslims in Medan City.